2001
DOI: 10.4310/hha.2001.v3.n2.a4
|View full text |Cite
|
Sign up to set email alerts
|

Idempotents and Landweber exactness in brave new algebra

Abstract: We explain how idempotents in homotopy groups give rise to splittings of homotopy categories of modules over commutative S-algebras, and we observe that there are naturally occurring equivariant examples involving idempotents in Burnside rings. We then give a version of the Landweber exact functor theorem that applies to M U -modules.In 1997, not long after [6] was written, I gave an April Fool's talk on how to prove that BP is an E ∞ ring spectrum or equivalently, in the language of [6], a commutative S-algeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Next we formulate the corresponding results for (highly structured) MGL-modules. In stable homotopy theory this viewpoint is emphasized in [20] and it plays an important role in this paper, cf. Section 9.…”
Section: Landweber Exact Theoriesmentioning
confidence: 99%
“…Next we formulate the corresponding results for (highly structured) MGL-modules. In stable homotopy theory this viewpoint is emphasized in [20] and it plays an important role in this paper, cf. Section 9.…”
Section: Landweber Exact Theoriesmentioning
confidence: 99%
“…as a product of two objects in CAlg(C), as observed in [May01]. To see this, we may reduce to the case when A = 1, by replacing C by Mod C (A).…”
Section: Example 223 Consider a Cartesian Diagram Of E ∞ -Ringsmentioning
confidence: 97%
“…We refer to such an object as a Landweber exact theory. May showed that such theories can be realized by MU -modules [33,Theorem 8], and Hovey-Strickland showed that there is a functorial lifting from the category of Landweber exact theories to the homotopy category of MU -modules [26]. In addition, there are results for L-algebras rather than L-modules.…”
Section: Realization Problemsmentioning
confidence: 99%